2018
DOI: 10.1371/journal.pone.0196553
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance to sudden noise by audio stimulation during early ontogeny in German shepherd puppies

Abstract: The period of early ontogeny constitutes a time when the physical immaturity of an organism is highly susceptible to external stimuli. Thus, early development plays a major role in shaping later adult behavior. The aim of the study was to check whether stimulating puppies at this early stage in life with sound would improve their responsiveness towards unfamiliar noises during the selection process of the police behavioral test for puppies. The cohort comprised 37 puppies from the litters of three mothers. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…As puppies develop, proper socialization through exposure to varied stimuli, ideally prior to 14 weeks of age, is key to the dog becoming a well-adjusted and resilient adult ( 54 ). Early, consistent experience with speech and music via radio clips ( 168 ) and video images ( 169 ) during the first few weeks of life have been linked to decreased noise reactivity and neophobia, respectively, around 7–8 weeks of age. Relatedly, a lack of exposure to urban environments between 3 and 6 months of age was associated with aggressive and avoidant behaviors ( 170 ).…”
Section: What Factors Will Optimize the Process Of Placing Successful Working Dogs?mentioning
confidence: 99%
“…As puppies develop, proper socialization through exposure to varied stimuli, ideally prior to 14 weeks of age, is key to the dog becoming a well-adjusted and resilient adult ( 54 ). Early, consistent experience with speech and music via radio clips ( 168 ) and video images ( 169 ) during the first few weeks of life have been linked to decreased noise reactivity and neophobia, respectively, around 7–8 weeks of age. Relatedly, a lack of exposure to urban environments between 3 and 6 months of age was associated with aggressive and avoidant behaviors ( 170 ).…”
Section: What Factors Will Optimize the Process Of Placing Successful Working Dogs?mentioning
confidence: 99%
“…Finally, despite a number of publications on intervention to treat firework fears in dogs [510], an important issue that seems to be comparatively neglected is how to prevent fears of fireworks in dogs from developing in the first place. One study indicated that playing the radio during feeding time in German shepherd puppies between the ages of 16 and 32 days led to more favourable responses to sudden loud noises when tested in a puppy test at the age of seven weeks [25]. On the other hand, no beneficial effects of gradually increased auditory stimulation from the age of three weeks was found when 7-week old puppies (German shepherds, Belgian Malinois, Dutch shepherd, and crosses between these breeds) were exposed to sudden noises in a behaviour test [26].…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have focused on the effects of specific socialisation stimuli on behaviour, although these have not been linked to adult behaviour traits. Chaloupková et al (2018) [ 60 ] investigated only auditory socialisation techniques. They hypothesised that exposure to audio stimuli during early ontogeny would improve reactions to noise during the police test for selecting puppies.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences were found in the other tests, suggesting that other aspects of the puppies’ rearing influenced their ability to cope with the other audio stimuli. This study highlights the importance of considering different sensory modalities when socialising a puppy [ 60 ].…”
Section: Discussionmentioning
confidence: 99%